A Framework for Ethical Payment to Research Participants - Gelinas, Luke; Largent, Emily A; Cohen, I. Glenn; Kornetsky, Susan; Bierer, Barbara E; Fernandez Lynch, Holly (The New England journal of medicine, 2018)
The authors propose a framework for evaluating the appropriateness of payments to research participants. They distinguish three acceptable rationales for payment: out-of-pocket expenses, time and burdens of participation, and incentive to participate.